Estudo sobre o efeito da densidade de plantas e espaçamento entre linhas na cultura do milho - Costa, Thiago Marques (Universidade Federal de São Carlos, 2021)
Corn (Zea mays L.) is one of the world’s most important crops its cultivation has great economic importance, and for the population’s food. In Brazil, the cereal has great relevance for several productive sectors and presents excellent production indexes due to its variety and adaptability to the conditions of the country. Several technologies have been approached in order to optimize the profitability and productivity of corn. The spatial arrangement and reduced spacing between lines are methodologies adopted for manipulating the distribution of plants and which may impact the characteristics of interest to the crop. Increments of agronomic performance and positive response in production are found in experiments with studies of densities and spacing. Studies have shown increases in the interception of solar radiation, better use of the energy resource in the canopy, reduced competitiveness and better use of natural resources in the management of the distance between plants. It was found that a reduction in the spacing between lines of corn in the studies used, a trend of positive effect on crop productivity.
Study on the effect of plant density and row spacing in corn crop
Keywords: Zea mays; Produtividade; População; Arranjo; OUTROS